Altered Amygdala Resting-State Functional Connectivity in Post-Traumatic Stress Disorder - Rabinak, Christine A.; Angstadt, Mike; Welsh, Robert C.; Kennedy, Amy; Lyubkin, Mark; Martis, Brian; Phan, K. Luan (Frontiers in Psychiatry, 2011)
Post-traumatic stress disorder (PTSD) is often characterized by aberrant amygdala activation and functional abnormalities in corticolimbic circuitry, as elucidated by functional neuroimaging. These ‘activation’ studies have primarily relied on tasks designed to induce region-specific, and task-dependent brain responses in limbic (e.g., amygdala) and paralimbic brain areas through the use of evocative probes such as personalized traumatic script-driven imagery and other negatively valenced emotional stimuli (e.g., threatening faces, aversive scenes, traumatic cues). It remains unknown if these corticolimbic circuit abnormalities exist at baseline or ‘at rest’, in the absence of fear/anxiety-related provocation and outside the context of task demands. Recently, a new approach to studying functional interconnectivity of brain regions derived from ‘resting state’ scans has elucidated systems-level neural network function that may be obscured by activation tasks and may help inform functional interpretations of brain activation patterns. Little is known about whether altered amygdala connectivity patterns exist at rest in PTSD. Therefore the primary aim of the present experiment was to investigate aberrant amygdala functional connectivity patterns in combat-related PTSD patients during resting state. Seventeen Operation Enduring Freedom/Operation Iraqi Freedom (OEF/OIF) veterans with combat-related PTSD (PTSD group) and seventeen combat-exposed OEF/OIF veterans without PTSD (Combat-Exposed Control [CEC] group) underwent an 8-minute resting-state functional magnetic resonance imaging scan. Using conventional methods to generate connectivity maps, we extracted the time series from an anatomically-derived amygdala ‘seed’ region and conducted voxel-wise correlation analyses across the entire brain to search for group differences (between PTSD and CEC groups) in amygdala functional connectivity, which we hypothesized would localize to the medial prefrontal cortex, anter